Western blotting: principles, applications, and techniques - Gomes, Aldrin V. (Henry Stewart Talks, 2024)
Proteomic studies, Gel electrophoresis, Western blotting: steps, Troubleshoots in western blotting, Blocking reagents, Normalization using housekeeping proteins, Antibody concentration, Quantification in western blotting, Advantages and disadvantages of western blotting